2017
DOI: 10.2147/ijwh.s90753
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on fetal and neonatal alloimmune thrombocytopenia – increasing clinical concerns and new treatment opportunities

Abstract: Differences in platelet type between the fetus and the mother can lead to maternal immunization and destruction of the fetal platelets, a condition named fetal and neonatal alloimmune thrombocytopenia (FNAIT). FNAIT is reported to occur in ~1 per 1,000 live born neonates. The major risk is intracranial hemorrhage in the fetus or newborn, which is associated with severe neurological complications or death. Since no countries have yet implemented a screening program to detect pregnancies at risk, the diagnosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 135 publications
(197 reference statements)
0
19
1
2
Order By: Relevance
“…The period incidence of neonatal thrombocytopenia evident in this study was higher than some figures reported in the literature. 9 , 20 However, a Turkish study reported that their 3-year period incidence of neonatal thrombocytopenia was 208/2218 (9.4%) between 2009 and 2012, 21 which is much higher than the incidence observed in this study. As previously reported, the incidences vary between different study populations, and the Saudi Arabian population in general has distinctive characteristics.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The period incidence of neonatal thrombocytopenia evident in this study was higher than some figures reported in the literature. 9 , 20 However, a Turkish study reported that their 3-year period incidence of neonatal thrombocytopenia was 208/2218 (9.4%) between 2009 and 2012, 21 which is much higher than the incidence observed in this study. As previously reported, the incidences vary between different study populations, and the Saudi Arabian population in general has distinctive characteristics.…”
Section: Discussioncontrasting
confidence: 76%
“…For instance, neonatal thrombocytopenia that developed in the second or third trimesters can be linked to preeclampsia, prematurity, congenital infections, chronic fetal hypoxia, low maternal platelet count, or a history of thrombocytopenia in prior pregnancies. 7 9 Others were immune related, such as auto- or alloimmune thrombocytopenia, disorders caused by the platelet opsonization with fetal or maternal antibodies that destroy human platelet antigens in fetuses. 10 In fetomaternal alloimmune thrombocytopenia, neonates are the only ones affected but generally endure mild symptoms such as petechial and other skin lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal and neonatal thrombocytopenia (FNAIT) is a potentially devastating disease that may cause neonatal intracranial hemorrhage, significant long‐term neurological sequela, or death 1,2 . Occurring in up to 1 per 1000 live born neonates, the leading cause is alloimmune whereby antibodies are created via maternal sensitization to paternally derived antigens expressed on fetal platelets that cross the placenta and destroy platelets 3,4 . The majority of FNAIT is caused by antihuman platelet antigen (HPA)‐1a (80%) and HPA‐5b (10‐15%).…”
Section: Figurementioning
confidence: 99%
“…HPA‐15 is localized on the platelet membrane protein CD109 [a glycosylphosphatidylinositol (GPI)‐linked glycoprotein located on the plasma membrane and belonging to the transforming growth factor‐β receptor system] . GPIIb‐IIIa integrin also harbours the HPA‐1a/b antigens, the most clinically relevant platelet antigens in foetal or neonatal alloimmune thrombocytopenia (FNAIT) which is a potentially devastating bleeding disorder resulting in destruction of foetal platelets and which occurs when an HPA‐negative mother is pregnant with a HPA‐positive foetus and becomes alloimmunized against the foetal HPA antigens, upon mixing of foetal blood with the mother's blood . This results in the formation of anti‐HPA‐specific IgG‐alloantibodies, which cross the placenta and destroy the foetal or neonatal platelets.…”
Section: Platelets As Both Prey and Predatormentioning
confidence: 99%